Mortality Associated with Recurrent Extreme Hyperferritinemia in Critically Ill Adolescents - John Scott Baird (International Journal of Inflammation)
Introduction. Recurrent extreme hyperferritinemia (ferritin >10,000 ng/mL) was noted in 4 critically ill adolescents prior to death, though this association has not previously been described. Methods. A retrospective review of the medical records of 4 critically ill adolescents with recurrent extreme hyperferritinemia and systemic inflammation was performed to identify additional common epidemiologic factors. Results. Systemic inflammation was characterized as cytokine storm syndrome in 2 patients and hemophagocytic lymphohistiocytosis in 2 patients. Episodes of extreme hyperferritinemia were noted on at least 2 different dates in all patients; these episodes (n = 10) were separated by an interval of 2 weeks to several months and were usually (in 8 of 10 episodes) associated with the onset or worsening of multiple organ dysfunction syndrome. Death occurred within 2 weeks of the onset of an episode of recurrent extreme hyperferritinemia. Lymphocytopenia and cachexia were noted in all patients. Conclusions. Recurrent extreme hyperferritinemia—often with multiple organ dysfunction syndrome—was noted in 4 adolescents with systemic inflammation who did not survive their critical illness. Recurrent extreme hyperferritinemia may be a novel biomarker of increased mortality in patients with the syndrome of persistent inflammation, immunosuppression, and catabolism.